Collagen Receptor Signaling in Platelets and Megakaryocytes - Watson, Steve P. (Thrombosis and Haemostasis, 1999)
The extracellular matrix protein, collagen, plays a primary role in hemostasis. Collagen fibers provide an important site for adhesion of platelets to the exposed subendothelium, trapping them at the site of vascular damage and enabling the formation of a monolayer of cells over the damaged area. Collagen fibers also stimulate platelet activation, leading to inside-out regulation of the integrin glycoprotein (GP) IIb-IIIa (also known as αIIbβ3), secretion from dense and α granules, generation of thromboxanes, and expression of procoagulant activity, all of which support the hemostatic process. The role of collagen in supporting platelet adhesion to the subendothelium is mediated through indirect and direct interactions. The indirect interaction is mediated through von Willebrand factor (vWF), which binds to the GP Ib-IX-V complex on the platelet surface.1-3 The interaction with vWF is critical for platelet adhesion at medium to high rates of flow because of the fast rate of association between vWF and GP Ib-IX. The importance of this interaction is demonstrated by the severe bleeding problems experienced by individuals with functional impairment of vWF (von Willebrand disease) or GP Ib-IX (Bernard-Soulier syndrome). At low rates of flow, collagen fibers are able to support adhesion in the absence of vWF through a direct interaction with a number of platelet surface glycoproteins i.e. collagen receptors,4,5 this also serves to support vWF-dependent adhesion at higher rates of flow by preventing dissociation. Crosslinking of platelet surface glycoproteins by collagen also generates intracellular signals, leading to platelet activation.The number of proteins on the platelet surface proposed to be collagen receptors is approaching double figures, but it is generally accepted that the integrin GP Ia-IIa (also known as α2β1) and glycoprotein VI (GP VI) are among the most important of these, playing critical roles in adhesion and activation, respectively6 (Fig. 1). This is illustrated by the mild bleeding problems of patients with a low level of expression or the presence of autoantibodies to GP Ia-IIa and the spontaneous, severe bleeding episodes that are occasionally seen in patients whose platelets are deficient in GP VI.6 There is evidence, however, that other collagen receptors have supporting roles in adhesion and activation. For example, GP VI supports platelet adhesion to collagen7 and GP IV, also known as CD36, may also play a similar role.8 The role of the recently cloned collagen receptor p65 in adhesion is not known. Evidence that the interaction of collagen with receptors, such as GPIV and p65, is of less importance than for interactions with GP Ia-IIa, and GP VI is provided by the absence of individuals with bleeding problems caused by deficiencies in these proteins. This is illustrated most clearly for GP IV, which is absent in 3% to 5 % of the Japanese population, and yet such individuals display no major vascular problems.Due to the large number of glycoproteins that bind collagen on the platelet surface, it has been difficult to gain a full understanding of the role of individual collagen receptors in adhesion and activation responses. This is complicated further by the interactions between vWF and GP Ib-IX-V, vWF or fibrinogen to activated GP IIb-IIIa especially as both glycoprotein receptors generate intracellular signals. The relative importance of individual collagen receptors in adhesion also varies with the rate of flow and between collagen types. A full discussion of platelet adhesion to collagen is beyond the scope of this article, and the reader is referred to a number of excellent recent reviews for further information.4-6,9,10 The present chapter focuses on the signaling events generated by the activation (or more correctly crosslinking) of platelet surface glycoproteins by collagen and the implications that this has for platelet activation under normal and diseased conditions.